Effect of alkali activation thin film transistor-liquid crystal display waste glass on the mechanical behavior of geopolymers. (20th February 2018) - Lo, Kang-Wei; Lin, Kae-Long; Cheng, Ta-Wui; Shiu, Hau-Shing
Highlights: Geopolymerization system network of geopolymers were examined with different alkaline reagents. Effects of the alkaline reagents and replacement levels of waste glass on mechanical behavior of geopolymers. Geopolymer with 0% waste glass and an S/N ratio of 2.0 is shown for 60-days of curing had the highest flexural strength. Thin film transistor liquid crystal display waste glass can be used as a reinforcement or a filler for geopolymers. Abstract: This study investigated the effect of thin film transistor liquid crystal display waste glass (TLWG) (0–40 wt%) and SiO2 /Na2 O (S/N) ratio on the properties of metakaolin-based geopolymers (MKGP). The MKGP with 0% TLWG and an S/N ratio of 2.0 is shown for 60-days of curing had the highest flexural strength (10.4 MPa); increasing the S/N ratio was discovered to increase the low resonance frequency of the geopolymers. When the MKGP with TLWG replacement was measured using nuclear magnetic resonance spectroscopy, the peak frequency is −82.0 to −86.3 ppm. When the TLWG replacement level was increased from 10% to 40%, after a curing time of 28 days, the weight loss of MKGP from 230 to 400 °C increased from 16.11% to 25.64%. As the S/N ratio was increased from 1.6 to 2.0, after a curing time of 60 days, the weight loss of MKGP between 230 and 400 °C was observed to increase from 14.61% to 14.94%. However, the weight loss from 600 °C to 750 °C decreased from 2.17% to 0.31%. MKGP with 0–10% TLWG and an S/N ratio of 2.0 has the potential to partially replace metakaolin as a geopolymer material contained more structural denser beneficial to structure development.